2013
DOI: 10.1159/000353116
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Ability of Human Developing and Differentiated Dental Mesenchyme

Abstract: The development of cell-based therapeutic strategies to bioengineer tooth tissue is a promising approach for the treatment of lost or damaged tooth tissue. The lack of a readily available cell source for human dental epithelial cells (ECs) severely constrains the progress of tooth bioengineering. Previous studies in model organisms have demonstrated that developing dental mesenchyme can instruct nondental epithelium to differentiate into enamel-forming epithelium. In this study, we characterized the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…We have previously shown that hESCs can be chemically induced to differentiate into ES-ECs that share similarities with dental epithelial cells 15 . Moreover, by co-culture with dental papilla cells in vitro and in vivo , ES-ECs can be further induced into ameloblast-lineage cells that express amelogenin 16 . In the future, adult dental pulp cells may be used in enamel regeneration following modification of their growth factor expression profiles ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that hESCs can be chemically induced to differentiate into ES-ECs that share similarities with dental epithelial cells 15 . Moreover, by co-culture with dental papilla cells in vitro and in vivo , ES-ECs can be further induced into ameloblast-lineage cells that express amelogenin 16 . In the future, adult dental pulp cells may be used in enamel regeneration following modification of their growth factor expression profiles ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that human embryonic stem cell-derived epithelial cells (ES-ECs) are similar to ameloblast-lineage cells 15 and that the developing human dental mesenchyme from the bell stage possesses the required signal to induce these ES-ECs to differentiate into dental epithelial cells 16 . This and other previous investigations have broadened the possibilities of cell-based enamel regeneration.…”
mentioning
confidence: 99%
“…Co-culture of human epithelial cells with mature dental pulp from erupted human teeth formed acinar type epithelial structures, similar to those found when ameloblast lineage cells were cultured alone. 57 - 58 These studies show the promise of human embryonic epithelial cells as a source for ameloblasts, and they raise the possibility that if adult dental pulp cells could be reprogramed to an earlier stage of differentiation, co-culture of these cells could regenerate teeth.…”
Section: Tissues/3d Cell Culture/organoidsmentioning
confidence: 98%
“…Tooth organ germs with a 1:1 ratio of rat apical bud cells and dental pulp stromal cells exhibited the highest alkaline phosphatase activity and elicited tooth-like structures containing dentin, differentiated ameloblasts and odontoblasts, and enamel, whereas germs with a higher proportion of bud cells or pulp cells lacked odontoblasts or ameloblasts, respectively (Yu et al, 2008). Finally, hESC-derived ECs (CK14+) expressed amelogenin and formed primordial tooth-like structures when co-encapsulated with fetal dental pulp stromal cells in culture and after implantation to sub-renal capsules (Zheng et al, 2013).…”
Section: Tooth-mentioning
confidence: 99%